2020
DOI: 10.4102/sajhivmed.v21i1.1054
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent human immunodeficiency virus self-management: Associations with treatment adherence, viral suppression, sexual risk behaviours and health-related quality of life

Abstract: BackgroundAdolescents living with HIV (ALHIV) represent a growing proportion of the global population of people living with HIV. In 2018, 1 600 000 adolescents [1 100 000; 2 300 000] between the ages of 10 and 19 years were living with HIV. That year, 190 000 were newly infected. 1 Sub-Saharan Africa (SSA) has the highest burden of HIV: 89% of the world's ALHIV reside in this region. Of South Africa's (SA) estimated 460 000 ALHIV, 52 000 new infections and 5 600 AIDS-related deaths were reported in 2018. 1 Ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 29 publications
0
39
0
Order By: Relevance
“…Self-regulation, especially coping with a stigmatised condition such as HIV, is an important component of HIV self-management for adolescents. Social facilitation and active participation in care was shown to correlate with improved health-related quality of life and adherence amongst ALHIV in South Africa [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-regulation, especially coping with a stigmatised condition such as HIV, is an important component of HIV self-management for adolescents. Social facilitation and active participation in care was shown to correlate with improved health-related quality of life and adherence amongst ALHIV in South Africa [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…taking treatment and attending appointments) [ 11 ]. The self-management domains described in the IFSMT have been associated with better adherence, health-related quality of life and viral suppression amongst ALHIV [ 21 ]. The assumption is that addressing multiple self-management domains will lead to a larger effect on behavioural and health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“… 13 Higher levels of self-management were associated with treatment adherence, viral suppression and better health-related quality of life. 14 …”
Section: Introductionmentioning
confidence: 99%
“…The viral suppression rate in this study is higher than that of a study done in Kenya which reported a 59% viral suppression among HIV positive adolescents [ 20 ]. In addition, a study done in South Africa found a viral suppression rate of 65.1% among adolescents [ 21 ]. Similarly, a 62.5% proportion of adolescents were virally suppressed in a study conducted in Tanzania [ 12 ].…”
Section: Discussionmentioning
confidence: 99%